Social capital, innovation and growth: evidence from Europe - I. Semih Akçomak; Bas ter Weel (Institute for the Study of Labor (IZA), 2008)
This paper investigates the interplay between social capital, innovation and per capita income growth in the European Union. We model and identify innovation as an important mechanism that transforms social capital into higher income levels. In an empirical investigation of 102 European regions in the period 1990-2002, we show that higher innovation performance is conducive to per capita income growth and that social capital affects this growth indirectly by fostering innovation. Our estimates suggest that there is no direct role for social capital to foster per capita income growth in our sample of European Union countries.
Keywords: O1; 330; Social capital; innovation; economic growth; European Union; Social Capital; Wirtschaftswachstum; Innovation; EU-Staaten